2018
DOI: 10.1007/s10592-018-1095-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic admixture between captive-bred and wild individuals affects patterns of dispersal in a brown trout (Salmo trutta) population

Abstract: Genetic admixture between captive-bred and wild individuals has been demonstrated to affect many individual traits, although little is known about its potential influence on dispersal, an important trait governing the eco-evolutionary dynamics of populations. Here, we quantified and described the spatial distribution of genetic admixture in a brown trout (Salmo trutta) population from a small watershed that was stocked until 1999, and then tested whether or not individual dispersal parameters were related to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 88 publications
1
26
0
Order By: Relevance
“…We first compared genetic admixture between wild and captive-bred strains using STRUCTURE 2.3.1 [96] with the admixture model and the correlated allele frequency model, without prior population information. Twenty runs assuming two clusters (K = 2, in order to discriminate between wild and captive-bred individuals, see [94]) were performed with a burn-in period of 200,000 and 200,000 subsequent MCMC repetitions. The ten best runs (highest LnP(D) values) were compiled using CLUMPP [97] to obtain final averaged individual Q-values.…”
Section: Methodsmentioning
confidence: 99%
“…We first compared genetic admixture between wild and captive-bred strains using STRUCTURE 2.3.1 [96] with the admixture model and the correlated allele frequency model, without prior population information. Twenty runs assuming two clusters (K = 2, in order to discriminate between wild and captive-bred individuals, see [94]) were performed with a burn-in period of 200,000 and 200,000 subsequent MCMC repetitions. The ten best runs (highest LnP(D) values) were compiled using CLUMPP [97] to obtain final averaged individual Q-values.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Saint‐Pé et al. () showed that, in a brown trout ( Salmo trutta trutta ) population from a small French watershed stocked for decades, both the emigration propensity and the dispersal destination of individuals were influenced by their individual level of genetic admixture with the domestic strain. Nevertheless, when contemporary individual dispersal events cannot be identified, genetic approaches relying on the spatial distribution of allelic frequencies (e.g., measures of genetic differentiation) must carefully dissociate the influence of between‐site landscape processes (geographic distance and/or landscape resistance) impacting the transience phase from the influence of at‐site landscape processes (local carrying capacity, patch quality, etc.)…”
Section: How To Infer Environmental and Individual Effects On Non‐effmentioning
confidence: 99%
“…Studies investigating whether and how migratory behavior is affected by hybridization between different migratory forms are scarce. However, Saint-Pé et al (2018) investigated genetic structure and spatial patterns of admixture in brown trout (S. trutta) within a small watershed in France, and report that dispersal was admixture-biased. In conclusion, populations can differentiate rapidly, selection can modify migratory behavior, and admixture between different migratory forms can impact on dispersal probability, population differentiation and genetic structure of migratory fish.…”
Section: Genetic Admixturementioning
confidence: 99%